The The Effect of Intellectual Capital on Financial Performance with Financial Disstress as a Moderation Variable - Devanti Kartikasari; Fetria Eka Yudiana (Sunan Kalijaga: Islamic Economics Journal, 2023)
Increase performance company is objective main for company For attract investors. Financial performance can be used by management to make decisions. Financial performance information is very important for investors as a tool for choosing investments (Rambe, 2020). The company's financial performance shows its ability to use the existing resources of the company as well as possible in order to generate profit or income. Objective from study This is For know influence of intellectual capital, sales growth and leverage to performance finances, and know is financial distress can moderate relationship between independent and dependent variables. Population in study This is company registered manufactures _ in Indonesian Sharia Stock Index (ISSI) and obtained sample as many as 20 companies. Study This using multiple linear regression techniques and Moderating Regression Analysis (MRA) with application eviews . Research results This showing that influential intellectual capital positive significant to performance finance , sales growth No influential to performance finance , leverage significant negative effect to performance finance , financial distress capable moderate influence intellectual capital to performance finance , financial distress No capable moderate influence sales growth to performance finance, financial distress No capable moderate influence leverage to performance finance.